2019
DOI: 10.12659/msm.916019
|View full text |Cite
|
Sign up to set email alerts
|

Deletion Polymorphism of Angiotensin Converting Enzyme Gene is Associated with Left Ventricular Hypertrophy in Uighur Hypertension-Obstructive Sleep Apnea Hypopnea Syndrome (OSAHS) Patients

Abstract: Background This study aimed to explore the association of angiotensin converting enzyme (ACE) gene insertion/deletion polymorphisms with left ventricular hypertrophy (LVH) in Han and Uighur hypertension-OSAHS (obstructive sleep apnea hypopnea syndrome) patients in China. Material/Methods A total of 162 Han and 72 Uygur patients with hypertension-OSAHS were independently subdivided into an LVH group and a non-LVH (NLVH) group based on the left ventricular mass index. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…LVH progression results in the development of congestive heart failure, which is associated with great health and economic burdens (Yancy et al, 2013;Ponikowski et al, 2016;Cai et al, 2018). Prior studies have shown that the prevalence of LVH is higher in people with OSAHS than their counterparts without OSAHS (Sekizuka et al, 2017;Hanlon et al, 2019;Maitikuerban et al, 2019). In addition, there is a linear relationship between the severity of OSAHS and LVH (Cuspidi et al, 2019(Cuspidi et al, , 2020Krasińska et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…LVH progression results in the development of congestive heart failure, which is associated with great health and economic burdens (Yancy et al, 2013;Ponikowski et al, 2016;Cai et al, 2018). Prior studies have shown that the prevalence of LVH is higher in people with OSAHS than their counterparts without OSAHS (Sekizuka et al, 2017;Hanlon et al, 2019;Maitikuerban et al, 2019). In addition, there is a linear relationship between the severity of OSAHS and LVH (Cuspidi et al, 2019(Cuspidi et al, , 2020Krasińska et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…( 2019) показал, что аллель D I/D полиморфизма гена ACE связан с повышенным риском развития ГЛЖ [15]. Обследование китайцев также доказало причастность минорного аллеля этого гена к повышению ИММЛЖ [16]. Исследование L.N.…”
Section: Discussionunclassified